OVARIAN CANCER WITH SOLITARY BRAIN METASTASIS. A CLINICAL CASE OF PROLONGED (OVER 7 YEARS) COMPLETE REMISSION AFTER COMBINED TREATMENT - N. V. Sevyan; V. В. Каrakhan; D. R. Naskhletashvili; A. Kh. Bekyashev; S. B. Alieva; D. M. Bеlоv; E. V. Prоzоrеnко; A. A. Мitrоfаnоv; L. T. Mamedova (ABV-press, 2018)
The article presents a clinical case of long-term complete remission after combined treatment in patient with metastasis of ovarian cancer in the brain. Duration of remission after treatment was more than 7 years.